(untitled) (Contemporary Mathematics, 2024)
In this paper, we characterize the hypercyclic, mixing and chaotic conjugate multipliers on some reflexive spaces of analytic functions. Our results extend several well-known results in the existing literature. We present some nontrivial examples to show the validity of our results.